Intensified Arctic warming under greenhouse warming by vegetation–atmosphere–sea ice interaction - Jee-Hoon Jeong; Jong-Seong Kug; Hans W Linderholm; Deliang Chen; Baek-Min Kim; Sang-Yoon Jun (Environmental Research Letters, 2014)
Observations and modeling studies indicate that enhanced vegetation activities over high latitudes under an elevated CO _2 concentration accelerate surface warming by reducing the surface albedo. In this study, we suggest that vegetation-atmosphere-sea ice interactions over high latitudes can induce an additional amplification of Arctic warming. Our hypothesis is tested by a series of coupled vegetation-climate model simulations under 2xCO _2 environments. The increased vegetation activities over high latitudes under a 2xCO _2 condition induce additional surface warming and turbulent heat fluxes to the atmosphere, which are transported to the Arctic through the atmosphere. This causes additional sea-ice melting and upper-ocean warming during the warm season. As a consequence, the Arctic and high-latitude warming is greatly amplified in the following winter and spring, which further promotes vegetation activities the following year. We conclude that the vegetation-atmosphere-sea ice interaction gives rise to additional positive feedback of the Arctic amplification.